Climate-smart crop-livestock systems for smallholders in the tropics: integration of new forage hybrids to intensify agriculture and to mitigate climate change through regulation of nitrification in soil - Rao, Idupulapati M.; Ishitani, Manabu; Miles, John W.; Peters, Michael; Tohme, Joseph M.; Arango, Jacobo; Moreta, Danilo E; López, Hernán; Castro, Aracely; Hoek, Rein van der; Martens, Siriwan D.; Hyman, Glenn G.; et al. (International Center for Tropical Agriculture, 2014)
It is widely recognized that less than 50% of applied nitrogen (N) fertilizer is recovered by crops and,based on current fertilizer prices,the economic value of this "wasted" N globally is currently estimated as US$81 billion annually. Worse still, this "wasted" N has major effects on the environment (Subbarao et al.2012). CIAT researchers and their collaborators in Japan reported a major breakthrough in managing N to benefit both agri-culture and the environment (Subbarao et al.2009). Termed "Biological Nitrification Inhibition" (BNI),this natural phenomenon has been the subject of long-term collaborative research that revealed the mechanism by which certain plants (especially the tropical pasture grass Brachiaria humidicola) naturally inhibit the conversion of N in the soil from a stable form to forms subject to leaching loss (NO3) or to the potent greenhouse gas N2O (Subbarao et al. 2012). B.humidicola, which is well adapted to the low-nitrogen soils of South American savannas, has shown high BNI capacity among the tropical grasses tested (Subbarao et al.2007). The major inhibitor in Brachiaria grasses is brachialactone, a cyclic diterpene (Subbarao et al.2009). Reduction of N loss from the soil under a B. humidicola pasture has a direct and beneficial environmental effect. We hypothesize that this conservation of soil N will have an additional positive impact on a subsequent crop (e.g. maize). At present, recovery of fertilizer N and the impact on crop yield is not known. The main purpose of our interinstitutional and multidisciplinary project, targeting small-scale farmers, is to develop the innovative approach of BNI using B. humidicola hybrids to realize sustainable economic and environmental benefits from integrated crop-livestock production systems.